(untitled) (Journal of the College of Basic Education, 2022)
Frankenstein (1816) is an impressive novel known as a story of terror, and many critics and movies present it to mean so. But, Mary Shelley (1797 – 1851), in her preface in the revised edition of 1831, describes the novel as: "one which speaks to the mysterious fears of our nature". 1 [emphasis added]. That is,